Successful Management of Quadriceps Contracture in a Cat Using a Dynamic Flexion Apparatus - Liptak, J.M.; Simpson, D.J. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
A comminuted, grade I open femoral fracture in an immature cat was repaired using stacked veterinary cuttable plates in a bridging fashion. The cat subsequently developed quadriceps contracture with stifle hyperextension and atrophy of the quadriceps muscle. Adhesions between the quadriceps muscle and fracture callus were released and a dynamic flexion apparatus used to prevent recurrence of quadriceps contracture by encouraging leg use and lengthening of the quadriceps muscles. The range of motion in the stifle improved from 35° to 130° and the cat maintained excellent use of the leg without recurrence of quadriceps contracture. Quadriceps contracture was diagnosed in an immature cat after biological repair of a comminuted femoral fracture using stacked veterinary cuttable plates in a bridging fashion. The quadriceps contracture was successfully managed with release of adhesions between the vastus intermedius and fracture callus, application of a dynamic flexion apparatus, and an intensive physiotherapy program.
Keywords: Quadriceps contracture; femoral fracture; biological repair; dynamic Oexion apparatus